Globalization and Economic Growth in Southeast Asian countries: The Role of Trade Openness and Foreign Direct Investment - Nguyen, Tan; Nguyen-Thu, Thuong; Luu-Huu, Duc (Acciones e Investigaciones Sociales, 2025)
This study explores the impact of trade openness and foreign direct investment (FDI) on economic growth and sustainable socioeconomic development in Southeast Asian countries, considering their diverse economic structures and policy frameworks. Utilizing panel ARDL methods, the findings demonstrate that trade openness and FDI significantly drive economic growth, with differential effects across the region. Advanced economies like Singapore and Brunei capitalize on robust financial systems and global market integration to maximize economic benefits. Industrializing nations, including Malaysia, Thailand, Indonesia, Vietnam, and the Philippines, leverage FDI and export growth but face challenges from inadequate infrastructure and governance issues, limiting equitable socioeconomic outcomes. Less-developed countries such as Myanmar, Laos, Cambodia, and Timor-Leste struggle to harness globalization’s potential due to weak industrial bases and institutional barriers, exacerbating vulnerabilities to market volatility. The study underscores the need for robust economic policies, transparent governance, and sustainable strategies to balance economic growth with social inclusion and environmental protection, contributing to resilient socioeconomic development in Southeast Asia.